Enhancing sleep quality in synucleinopathies through physical exercise - Canonichesi, Jacopo; Bellingacci, Laura; Rivelli, Francesco; Tozzi, Alessandro (Frontiers in Cellular Neuroscience, 2025)
During sleep, several crucial processes for brain homeostasis occur, including the rearrangement of synaptic connections, which is essential for memory formation and updating. Sleep also facilitates the removal of neurotoxic waste products, the accumulation of which plays a key role in neurodegeneration. Various neural components and environmental factors regulate and influence the physiological transition between wakefulness and sleep. Disruptions in this complex system form the basis of sleep disorders, as commonly observed in synucleinopathies. Synucleinopathies are neurodegenerative disorders characterized by abnormal build-up of α-synuclein protein aggregates in the brain. This accumulation in different brain regions leads to a spectrum of clinical manifestations, including hypokinesia, cognitive impairment, psychiatric symptoms, and neurovegetative disturbances. Sleep disorders are highly prevalent in individuals with synucleinopathies, and they not only affect the overall well-being of patients but also directly contribute to disease severity and progression. Therefore, it is crucial to develop effective therapeutic strategies to improve sleep quality in these patients. Adequate sleep is vital for brain health, and the role of synucleinopathies in disrupting sleep patterns must be taken into account. In this context, it is essential to explore the role of physical exercise as a potential non-pharmacological intervention to manage sleep disorders in individuals with synucleinopathies. The current evidence on the efficacy of exercise programs to enhance sleep quality in this patient population is discussed.